An American plague : the true and terrifying story of the yellow fever epidemic of 1793 - Murphy, Jim, 1947- (New York : Clarion Books, 2003)
Provides an account of the yellow fever epidemic that swept through Philadelphia in 1793, discussing the chaos that erupted when people began evacuating in droves, leaving the city without government, goods, or services, and examining efforts by physicians, the Free African Society, and others to cure and care for the sick.
No one noticed -- "All was not right" -- Church bells tolling -- Confusion, distress, and utter desolation -- "It was our duty" -- The prince of bleeders -- "By twelve only" -- "This unmerciful enemy" -- "A delicate situation" -- Improvements and the public gratitude -- "A modern-day time bomb."
Includes bibliographical references (p. 141-153) and index.
Publisher's Weekly
Kirkus Starred
7.1
5-8
Newbery 2004 Medal
Keywords: Yellow fever -- Pennsylvania -- Philadelphia -- History -- 18th century -- Juvenile literature; Yellow fever -- Pennsylvania -- Philadelphia -- History -- 18th century; Pennsylvania -- History -- 1775-1865.; Yellow fever -- History; Pennsylvania -- History